Legal Protection for Indigenous Communities That Conduct Tajen That Contain Elements of Gambling - I Gde Daniel Rafael Putra Djatimulia; Abraham Ferry Rosando (Jurnal Mengkaji Indonesia, 2026)
Abstract: This study examines the conflict between Balinese customary law, particularly tajen as the tabuh rah ritual in Hindu ceremonies, and national criminal law that prohibits gambling under Article 303 of the KUHP and Law No. 7 of 1974. Tajen is not merely gambling but an integral part of bhuta yadnya, aimed at neutralizing negative energies. It is recognized in the awig-awig of desa pakraman and the philosophy of Tri Hita Karana. However, the betting element leads to the criminalization of indigenous communities, creating legal uncertainty. The research problems include the current legal protection and the negative function of material unlawfulness based on Article 2 of Law No. 1 of 2023 on the Criminal Code. Using a normative method with statutory and conceptual approaches, this study analyzes primary legal sources such as Article 18B paragraph (2) of the 1945 Constitution, Law No. 6 of 2014 on Villages, and jurisprudence such as Constitutional Court Decision No. 58/PUU-XV/2017. The findings indicate that legal protection is partial: constitutionally, it recognizes customary rights, but implementation is weak due to the absence of regional normative regulations. Theories of legal pluralism and substantive justice support harmonization, where the negative aspect of material unlawfulness can eliminate criminal liability if tajen is purely ritualistic without commercial elements. The conclusion recommends reformulating norms through a Bali Regional Regulation to legalize ritual tajen, issuing customary certificates, and applying restorative justice, to realize substantive justice in the multicultural Unitary State of the Republic of Indonesia. Purpose: This article aims to analyze whether the tajen on the Island of Bali, which contains elements of criminal acts (namely gambling), allows the perpetrators of these customary activities to receive legal protection from the perspective of criminal law and the position of customary law in Indonesia. Design/Methodology/Approach: This article employs a normative legal research approach by examining relevant laws and regulations as well as academic literature concerning legal protection for indigenous communities engaged in tajen that involve elements of gambling. Findings: This study finds that customary activities involving gambling elements, known as tajen, create conflicts between customary law and criminal law in Indonesia. Tajen, as a traditional customary practice, leads to the criminalization of indigenous communities. The indigenous people themselves conduct tajen based on the understanding that it is a customary activity intended to stimulate the village economy across Bali. However, on the other hand, this activity also contains elements of criminal acts, namely, gambling. The absence of regional regulations that serve to recognize this customary activity and provide a legal umbrella for indigenous communities is a critical missing factor, as it contradicts Article 18B of the 1945 Constitution of the Republic of Indonesia. Originality/value: This article offers an original contribution by examining the activities of the traditional Balinese custom known as tajen, which involves elements of gambling and has a direct impact on indigenous Balinese communities. To date, there remains no clear legal regulation governing this practice. This issue actually represents an aspect that frequently causes